2012
DOI: 10.1108/10650741311288797
|View full text |Cite
|
Sign up to set email alerts
|

Ontology‐driven disability‐aware e‐learning personalisation with ONTODAPS

Abstract: PurposeThe purpose of this paper is to show how personalisation of learning resources and services can be achieved for students with and without disabilities, particularly responding to the needs of those with multiple disabilities in e‐learning systems. The paper aims to introduce ONTODAPS, the Ontology‐Driven Disability‐Aware Personalised E‐Learning System, which has the mechanism for such personalisation.Design/methodology/approachThis paper reviews current e‐learning systems that provide personalisation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…There are efforts being made through research to improve access to learning materials for students with disabilities (Nganji et al, 2013b). However, although much of the material needed for courses is usually located in the learning management systems, students may be referred to materials available elsewhere, including journal articles published in PDF.…”
Section: Problem Statementmentioning
confidence: 99%
“…There are efforts being made through research to improve access to learning materials for students with disabilities (Nganji et al, 2013b). However, although much of the material needed for courses is usually located in the learning management systems, students may be referred to materials available elsewhere, including journal articles published in PDF.…”
Section: Problem Statementmentioning
confidence: 99%
“…prior knowledge of learners background, learning behaviour and actions when using the system. The system should also be capable to dynamically updat e the representation of users performance taking into account the changing state of the leaners and the variations in information that is relevant to each user considering the fact that there is an additional task of matching such learners (user profiles) with solutions that best fits their particular learning needs/requirement (Nganji et al, 2013). According to (Huang and Shiu, 2012;Nganji et al, 2011) the key challenge in developing automated system for learning is to build effectively represented user profile, learning styles and goal to help support reasoning about each learner.…”
Section: User-centric Design Model Towards Enhancement Of E-learning mentioning
confidence: 99%
“…That being said, this simple test indicated that recommendations individualized for each student did help him or her to increase their knowledge and guide them through their learning process. Similar to patient-prescription-healing relation, the designed system offer student-personal recommendation-learning model (Kumaran & Sankar, 2013;Nganji et al, 2011). …”
Section: Post-hoc Proceduresmentioning
confidence: 99%
“…A personalized E-learning system should: measure the student's knowledge on a subject, determine the concepts that need to be learned or reviewed, and provide essential content to the student. Supporting personalization in E-learning systems is one of the major benefits of using ontologies (Gaeta et al, 2009;Nganji, Brayshaw, & Tompsett, 2011;Ongenae et al, 2013;Yalcinalp & Gulbahar, 2010). There are adaptive systems designed to make personal recommendations by acquiring user's knowledge.…”
mentioning
confidence: 99%